Actions to prevent and identify fetal alcohol spectrum disorders to be implemented in general practice: a consensus - Leruste, Sébastien; Pouilley-Bax, Alice; Doray, Bérénice; Maillard, Thierry; Monin, Frédérick; Loubaresse, Coralie; Marimoutou, Catherine; Spodenkiewicz, Michel (Frontiers in Medicine, 2024)
Introduction: Fetal alcohol exposure is the most common preventable cause of non-genetic intellectual disability. Fetal Alcohol Syndrome (FAS) is characterized by intellectual disability and distinctive facial features and affects 0.1% of live births, representing approximately 800 cases per year in France. Fetal Alcohol Spectrum Disorder (FASD) are ten times more common than FAS, with an estimated 8,000 cases per year, and are associated with behavioral and social maladjustment in both children and adults, as well as various malformations. General practitioners play a key role in preventing and identifying FASD through their involvement in pregnancy and child monitoring. Method: Qualitative study using the Delphi method. Items were developed from the literature and semi-structured interviews with field professionals and health institutions. A panel of multiprofessional experts, mostly general practitioners, was recruited. Results: 24 initial actions were submitted to the experts. At the end of the first round, 6 actions reached a consensus and 6 were reformulated for the second round. At the end of the second round, 3 actions reached a consensus, for a total of 11 consensus actions. Four of these actions seem particularly relevant for rapid implementation, namely systematic proposal of pre-conceptional consultations for women planning pregnancy, systematic identification of environmental factors during child monitoring, systematic distribution of information on fetal alcohol exposure during pre-conception or early pregnancy, and the publication of a leaflet for general practitioners on the identification of children with FAS or FASD and the contact details of relevant associations. Conclusion: Prevention and identification of FASD can be improved through short and general training supports for general practitioners. Early screening of FASD is crucial for children, and should be maintained throughout their monitoring. This study could be used for communication and dissemination of information based on the consensus obtained.